Cryptosporidium parvum decay during air drying and stockpiling of mesophilic anaerobically digested sewage sludge in a simulation experiment and oocyst counts in sludge collected from operational treatment lagoons in Victoria, Australia. - Kong,FE; Deighton,MA; Thurbon,NA; Smith,SR; Rouch,DA (Journal of Water and Health, 2018)
The inactivation of Cryptosporidium species oocysts during sewage sludge treatment is important to protect human health when the residual biosolids are applied to agricultural land. Quantifying the decay of Cryptosporidium species during sludge treatment for microbiological assurance purposes is difficult if low numbers are present in wastewater. The rate of decay of Cryptosporidium parvum oocysts during solar/air drying treatment and in sludge stockpiles in temperate environment conditions was simulated in laboratory inoculation experiments using sludge sampled from a mesophilic anaerobic digester. Oocyst numbers were also determined in settled lagoon sludge samples collected from three operational rural wastewater treatment plants (WWTPs). C. parvum oocysts were enumerated by immunomagnetic separation followed by staining with vital dyes and examination by confocal laser scanning microscopy. An air-drying/storage period equivalent to 11 weeks was required for a 1 log10 reduction of viable oocysts inoculated into digested sludge. Oocyst viability in air-dried and stored digested sludge decreased with time, but was independent of sludge desiccation and dry solids (DS) content. No oocysts were detected in sludge samples collected from the anaerobic digester, and the average concentration of oocysts found in settled lagoon sludge from the rural WWTP was 4.6 × 102 oocysts/g DS.